Numerical analysis and synthesis of Zno nanorods with various dopant concentrations for electron transport improvement in solar cell applications - Mohd Alias, Nur Syafiqah Nadiah (2023)
Dye-sensitized solar cell (DSSC) and Perovskite Solar Cell (PSC) are categorized as the third generation in solar cell technology. Both solar cells are known for its low production cost, simple preparation methodology, low toxicity, substrate flexibility and suitability for indoor use. In the previous two decades, PSC has shown a very encouraging rate of improvement in performance, rising from single digits to double digits rapidly. The Electron Transport Layer (ETL) plays an important role in PSC through charge extraction. TiO2 material has been used as an ETL conventionally, but the process of further improving the performance of PSC-based TiO2 ETL is nearly saturated and deadlocked. In theory, the ZnO material possesses an energy band gap value similar to the TiO2 material, but with superior electron mobility. This clearly shows the potential of ZnO material to replace TiO2 material acting as photoanode and ETL for DSSC and PSC, respectively. However, previous articles have reported that pure ZnO is still insufficient in improving the performance of solar cells. Herein, small amounts of Al and Ni dopants are added into the ZnO layers, believed to passivate the widely known Zn2+ lattice defect in the ZnO bulk layer. In addition, the structural features of ZnO nanorods also imply providing a higher surface aspect ratio allowing a greater charge carrier reaction mechanism. Initially, this work started with the simulation of complete DSSC and PSC utilizing the ZnO layer as the photoanode and ETL, respectively using SCAPS software. The Al and Ni dopant concentrations are varied in enhancing cell performance. Power conversion efficiency (PCE) as high as 3.96% and 3.9% were obtained using concentrations of 3 mol% and 4 mol% for ZnO:Al and ZnO:Ni photoanodes in DSSC, respectively. Meanwhile, PCE values of PSC reaching 17.6% and 17.58% were recorded from dopant concentration of 1 mol% for both ZnO:Al ETL and ZnO:Ni ETL, respectively. Compatibility with other layers was also studied, suggesting the use of Cu2O as the HTL and Pb-free CH3NH3SnI3 perovskite material as the absorber layer. It has been discovered that the combination of Al-doped ZnO ETL with Cu2O HTL and CH3NH3SnI3 absorber layer in PSC has successfully produced considerable PCE values as high as 27.72% and 21.18% for ZnO:Al ETL and ZnO:Ni ETL, respectively. Based on simulations and experimental evidence, the combination of a small amount of dopant into the ZnO layer with appropriate inorganic HTL and Pb-free perovskite layers is shown to be promising in enhancing the performance of the PSC. This study clearly has an impact in providing guidance to researchers and industry before the full fabrication process of solar cells is carried out.